2016
DOI: 10.1007/s13312-016-0954-5
|View full text |Cite
|
Sign up to set email alerts
|

Point of care neonatal ultrasound — Head, lung, gut and line localization

Abstract: Ultrasound performed by the clinician has an extensive role in the neonatal intensive care unit. Basic ultrasound knowledge of head, lung and gut is a useful supplement to clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
11
0
2
Order By: Relevance
“…Due to its non-invasive nature and to minimize radiation exposure, lung and abdominal ultrasonography is being increasingly used worldwide in adults and more recently, neonatal intensive care, for diagnosis of a variety of conditions such as pneumonia, pleural effusions, necrotising enterocolitis, etc., with fairly high sensitivity and specificity. 7, 18 Formal training curriculums and increased utilization in Indian NICUs would help increase expertise in this area over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its non-invasive nature and to minimize radiation exposure, lung and abdominal ultrasonography is being increasingly used worldwide in adults and more recently, neonatal intensive care, for diagnosis of a variety of conditions such as pneumonia, pleural effusions, necrotising enterocolitis, etc., with fairly high sensitivity and specificity. 7, 18 Formal training curriculums and increased utilization in Indian NICUs would help increase expertise in this area over time.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated its benefits in the day-to-day management of neonates. 6-8 Point-of-care ultrasonography in neonatal practice primarily includes cranial, lung, and abdominal ultrasound, “targeted” or “functional” echocardiography (fnECHO), and the use of ultrasound to locate the position of vascular catheters. 7, 9…”
Section: Introductionmentioning
confidence: 99%
“…Another pathological finding at LUS is the lung pulse, i.e., the synchronized movement of the pleura with the cardiac rhythm at M-mode US for the transmission of cardiac activity on lung parenchyma. It is not present in a normally aerated lung for the dominant action of lung sliding over the cardiac vibration, and if present, it is a sign of absence of ventilation [14]. Summarizing, a black appearance means healthy lung, a mixed black and white appearance is associated to a moderate disease, and a completely white lung is a marker of severe respiratory distress.…”
Section: Normal and Abnormal Findings At Lusmentioning
confidence: 99%
“…It is likely to be NEC when the bowel wall thickness is >2 mm; abnormal thinning with a thickness of <1.0 mm results from ischemia or necrosis. 33…”
Section: Physical Characteristicsmentioning
confidence: 99%